تأثر الترجمة باتجاه تفسيري عقدي معين: دراسة اختلاف الترجمات بين تفسير هداية الرحمن والقرآن وترجمة معانيه إلى اللغة الإندونيسية وتفسير محمود يون/ The influence of certain doctrinal exegesis on translation: A Study between Tafsir Pimpinan al-Rahman, Al-Qur’ - Mohd. Faizal bin Mohamad; Akmal Khuzairy bin Abd. Rahman , (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2022)
مُلخَّص البحث: يهدف هذا البحث إلى كشف وجوه الاختلاف في ترجمات الآيات المتشابهات بين تفسير هداية الرحمن الذي ألفه عبد الله باسميح، والقرآن وترجمة معانيه إلى اللغة الإندونيسية، وتفسير محمود يونس مقارناً بين هذه الترجمات. تعتمد الدراسة على المنهج الوصفي التحليلي باختيار عدد معين من النماذج وإخضاعها، للتحليل من أجل الكشف عن الاختلاف في هذه الترجمات الثلاثة في ترجمتها للآيات المتشابهات، فقد تبين من التحليل بأن هنالك ميولاً تفسيرياً معيناً من المترجمين إلى اتجاه عقدي معين، ومن الملاحظ أن هذه الميول تجعلهم يختارون المعنى المفسر المعين الذي يساير بالمنهج العقدي الذي يسير عليه، وقد استنتجت الدراسة بأن هنالك رابطاً قوياً بين اتجاه عقدي معين وبين المعنى الـذي اختاره المترجم في ترجمته، وأنهم لم يحاولوا ٌإدراج هذه المعاني المحتملة في ترجماتهم، بل عمدوا إلى أحد منها دون الآخر. الكلمات المفتاحية: المناهج التفسيرية، المترجمون، الآيات المتشابهات. Abstract This research aims to reveal the differences in the translation of similar verses between three different al-Quran’s translations, which are Tafsir Hidayat ar-Rahman written by Abdullah Basmeih, al-Quran and its Translation of its Meanings into Indonesia Language and The Tafsir Al-Quran al-Karim by Prof. Mahmud Yunos, comparing these translations. The research revealed the differences in these three translations in terms of the direction of the dogmatic interpretation that the translators tended to when translating similar verses. The problematic is that the translator’s tendencies with a doctrinal interpretation that makes translators chose the specific interpreted meaning that matches a certain ideological approach. The research followed a combined several approaches: The inductive method was used to reveal the views and tendencies of the exegetes in interpreting similar verses with a specific doctrinal interpretation. The researcher also used the analytical method to show the influence of the three translators towards the faith in translating similar verses. The study concluded that all translations have their own tendency to deal with the translation of these verses and are consistent with the method of authorization, interpretation, and confirmation of both the predecessors and the successors. Keywords: Exegetical approaches, Translators, Allegorical verses. Abstrak Kajian ini bertujuan untuk mendedahkan aspek-aspek perbezaan terjemahan ayat-ayat mutashabihat dengan membandingkan di antara tiga terjemahan al-Quran yang iaitu Tafsir Hidayat ar-Rahman karangan Abdullah Basmeih, al-Quran dan Terjemahannya ke dalam Bahasa Indonesia dan Tafsir Al- Quran al-Karim oleh Mahmud Yunos. Kajian ini menggunakan metod analisis dan deskriptif dengan memilih beberapa sampel dan menganalisanya untuk melihat perbezaan terjemahan ayat-ayat mutashabihat di antara ketiga-tiga terjemahan tersebut. Hasil analisa mendapati bahawa terdapat kecenderungan aliran akidah tertentu dalam kalangan para pentafsir tersebut yang membuatkan mereka memilih makna tafsiran yang sejajar dengan kecenderungan tersebut. Kajian ini merumuskan bahawa terdapat hubungan yang jelas di antara kecenderungan kepada mazhab aqidah tertentu dengan terjemahan-terjemahan tersebut. Mereka juga didapati tidak cuba untuk merangkumkan tafsiran yang berbeza dengan mazhab aqidah yang lain. Kata kunci: Pendekatan tafsir, Penterjemah, ayat-ayat mutashabihat.